1997
DOI: 10.1002/hep.510260309
|View full text |Cite
|
Sign up to set email alerts
|

Different changes in expression and function of connexin 26 and connexin 32 during DNA synthesis and redifferentiation in primary rat hepatocytes using a DMSO culture system

Abstract: recovery of GJIC measured by lucifer yellow was later thanIn the present study, we determined in detail the changes that of Cx32 expression. These results indicated the different of liver gap junctions, connexin 26 (Cx26), and connexin 32 changes of expression and function of Cx26 and Cx32 in the (Cx32), during DNA synthesis and redifferentiation of hepatohepatocytes during stimulation and re-inhibition of DNA syncytes in vitro. We used primary rat hepatocytes that expressed thesis. This culture system should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Gap junctions existing in the intercellular space play an important role in the intercellular signal transduction system. It was confirmed that there are two GJs in the liver (connexin 26 and 32), and connexin 32 accounts for the majority in the intralobular distribution of GJ, whereas the distribution of connexin 26 is limited to zones 1 and 2 alone (Kojima et al 1997, Neveu et al 1995, Stutenkemper et al 1992. Such differences in the distribution of GJ may induce differences in the distribution of LY dye.…”
Section: Fig 5 Serial Changes In the Bile Canalicular Fluorescence (mentioning
confidence: 90%
“…Gap junctions existing in the intercellular space play an important role in the intercellular signal transduction system. It was confirmed that there are two GJs in the liver (connexin 26 and 32), and connexin 32 accounts for the majority in the intralobular distribution of GJ, whereas the distribution of connexin 26 is limited to zones 1 and 2 alone (Kojima et al 1997, Neveu et al 1995, Stutenkemper et al 1992. Such differences in the distribution of GJ may induce differences in the distribution of LY dye.…”
Section: Fig 5 Serial Changes In the Bile Canalicular Fluorescence (mentioning
confidence: 90%
“…33 However, low concentrations of DMSO (1% to 2%) in the culture medium have been shown to support cell differentiation [34][35][36] and to increase infectivity of freshly isolated hepatocytes. 37 Here, we provide evidence that after stepwise reduction of DMSO, maintenance of 2% DMSO in culture not only improved attachment rates of thawed hepatocytes, but it allowed establishment of WHV infection in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…19 Interestingly, one of them, AML12, stably expressed mRNAs for Cx32 and Cx26, but nothing was reported about the relative proteins and their GJIC competence. Concerning hepatocytes in primary culture, although they express Cx32 and Cx26, 20 their GJIC is usually poor and may be sligthly improved either by treatment with dimethylsulfoxide (DMSO) 20,21 or by co-culture with fibroblasts. 22 Being interested in the modulation of GJIC of hepatocytes, we tried to find an in vitro cell system that efficiently communicates via liver-specific Cxs.…”
mentioning
confidence: 99%